2008
DOI: 10.1371/journal.pone.0002390
|View full text |Cite
|
Sign up to set email alerts
|

Artemether-Lumefantrine versus Dihydroartemisinin-Piperaquine for Treating Uncomplicated Malaria: A Randomized Trial to Guide Policy in Uganda

Abstract: BackgroundUganda recently adopted artemether-lumefantrine (AL) as the recommended first-line treatment for uncomplicated malaria. However, AL has several limitations, including a twice-daily dosing regimen, recommendation for administration with fatty food, and a high risk of reinfection soon after therapy in high transmission areas. Dihydroartemisinin-piperaquine (DP) is a new alternative artemisinin-based combination therapy that is dosed once daily and has a long post-treatment prophylactic effect. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
119
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 22 publications
16
119
1
Order By: Relevance
“…In this study, Pfmdr 1 S1034C allele was also observed but occurred at a lower frequency compared to Pfmdr 1 N86Y and Y184F while Pfmdr 1 N1042D allele was not observed in any of the patients tested. The absence of N1042D allele within the study group could not be explained, however a similar finding has been reported in other studies Dokomajila et al, 2006;Happi et al,2009 while our result differs from another study carried out in Ghana, where the prevalence of Pfmdr 1 N1042D allele was found to increase from 2003(Duah et al, 2013. It is worthy of note that it is the cumulative rather than individual effect of these Pfmdr 1 SNPs that contributed significantly (P<0.001) to artemether-lumefantrine resistance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, Pfmdr 1 S1034C allele was also observed but occurred at a lower frequency compared to Pfmdr 1 N86Y and Y184F while Pfmdr 1 N1042D allele was not observed in any of the patients tested. The absence of N1042D allele within the study group could not be explained, however a similar finding has been reported in other studies Dokomajila et al, 2006;Happi et al,2009 while our result differs from another study carried out in Ghana, where the prevalence of Pfmdr 1 N1042D allele was found to increase from 2003(Duah et al, 2013. It is worthy of note that it is the cumulative rather than individual effect of these Pfmdr 1 SNPs that contributed significantly (P<0.001) to artemether-lumefantrine resistance.…”
Section: Discussionsupporting
confidence: 86%
“…The role of genes such as Plasmodium falciparum chloroquine resistance transporter (Pfcrt), Pfmdr1 and Dihydrofolate reductase (dhfr) in antimalarial drug resistance has been studied (Falade et al, 2005). The efficacy and effectiveness of AL as an antimalarial drug has been reported (Falade et al, 2005;Yeka et al 2008;Zurovac et al, 2008). Recent reports from Africa have shown some evidence of clinical and parasitological failure after treatment with AL (Yang et al, 2003;Jambou et al, 2005;Noedl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, clinical trials in Africa and southeast Asia have documented excellent efficacy of DP for treatment of falciparum malaria. [25][26][27] More importantly, several comparative trials of DP versus AL in Africa revealed another advantage of DP in reducing the risk of recurrent parasitemia within 4-9 weeks of treatment. [26][27][28][29] However, clinical failure with DP was recently reported from Cambodia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Dihydroartemisinin-piperaquine (DP) is emerging as a favorable antimalarial option with comparable clinical efficacy to AL, prolonged post-treatment prophylaxis, and a simple once a day dosage regimen. [3][4][5][6] The ACTs appear to be well-tolerated and serious toxicities are rare. 1,4,5,7 Early vomiting (vomiting within one hour of dosing) has been reported in 3% of courses of AL 4 and DP 4,6 in adults.…”
mentioning
confidence: 99%
“…[3][4][5][6] The ACTs appear to be well-tolerated and serious toxicities are rare. 1,4,5,7 Early vomiting (vomiting within one hour of dosing) has been reported in 3% of courses of AL 4 and DP 4,6 in adults. However, this rate increased to 10% 6 or 11% 4 in children.…”
mentioning
confidence: 99%